Where Are the Dead? Celestial, Earthly and Subterranean Spaces in Juan Rulfo and José Revueltas (European Journal of Language and Literature, 2018)
Juan Rulfo (1917-1986) and José Revueltas (1914-1976) are two of the most important writers of the twentieth century for Mexican and worldwide literature. When comparing the literary work of both authors can be found similarities rich in meanings that help us to understand in a deep way a worldview of man from the finiteness of being, the subjugation to which men and their societies confront the power Political of their rulers, and the alienation of modern societies. These thematic similarities find throughout their literary work divergences in style and treatment of their plots and characters. In this way, in the paper I propose here, I expose in a wide way the biographical and bibliographic aspects that support the importance of these authors, and then analyze how in the literary work of Juan Rulfo –the novel: Pedro Páramo and his collection of short stories: El llano en llamas– and that of José Revueltas –novels: Los muros de agua, El luto humano, Los días terrenales, En algún valle de lágrimas, Los motivos de Caín, Los errores y El apando; and short story books: Dios en la tierra, Dormir en tierra y Material de los sueños– show that cosmogonic vision of the Mexican being in which the presence of death prevails and its meanings from three possible spaces: in the subterranean, the earthly and the celestial. In a graphical way I analyze and contrast how both writers develop in their literary work these three spaces, from the symbolic perspective of the death.